Syntax-Semantics Interface in Linguistic Theory - جمعة جمعة مؤيد; محمود الكواز زينب (Al-Adab Journal, 2018)
According to a process called selected focusing, the linguist in order to produce a coherent statement or an adequate description has to focus on one aspect of a language and exclude the others. Yet, such isolation is only an artificial element. A layman or a child does not have a least idea about the various levels of language. Yet, he is very-well equipped with the grammatical, structural, and semantic tools that help him to instantly identify the ill-formed or unmeaningful sentences of his native language as language is learned and taught as a whole. With regard to syntax-semantics interface in linguistic literature, two opposite mainstreams have been found; a syntactically- oriented perspective (Chomsky 1957, 65, 79, 81, Cullicover 1976, Radford 1988, Horrock 1987, and Haegman 1992) modified and supported later on by the Optimality Theory approach (henceforth OT) established by Alan Prince and Paul Smolensky (1993) and a semantically-oriented one in its two facets the generative and the interpretive (Jerrold J. Katz & Jerry A. Fodor: 1963, George Lakoff 1963) developed in some of its aspects by Charles Fillmore’s case grammar (1968). Furthermore, a great deal of effort has been proposed in line with these two opposite approaches to produce some experimental psycholinguistic and neurolinguistic studies to support or reject one or both of them (Millar & Mckean 1964, Savin & Perchonock 1965, and Clifton & Odom 1966, Gleason, J. & Ratner, N. 1993, Friederici, Angela D., & Jürgen Weissenborn 2007). The early generative transformational approach went too far in insisting that the syntactic aspect has an autonomous characteristic and should be dealt with in isolation from semantics; others argue that they are interrelated and cannot be separated. Some linguists as the generative semanticists consider semantics as more basic in grammatical description than syntax; whereas, others hold a totally reversed approach assuming that semantics cannot be described and it should be considered as an extra-linguistic element. This paper is at attempt to shed some light on this serious linguistic controversy to arrive at some general outlines that might help the linguistic theorists, language second/foreign teachers and students to establish a scientific scheme in dealing with language.